2D-crystal-based functional inks - Bonaccorso, Francesco; Bartolotta, Antonino; Coleman, Jonathan N.; Backes, Claudia (Advanced materials, 2016)
The possibility to produce and process graphene, related 2D crystals, and heterostructures in the liquid phase makes them promising materials for an ever-growing class of applications as composite materials, sensors, in flexible optoelectronics, and energy storage and conversion. In particular, the ability to formulate functional inks with on-demand rheological and morphological properties, i.e., lateral size and thickness of the dispersed 2D crystals, is a step forward toward the development of industrial-scale, reliable, inexpensive printing/coating processes, a boost for the full exploitation of such nanomaterials. Here, the exfoliation strategies of graphite and other layered crystals are reviewed, along with the advances in the sorting of lateral size and thickness of the exfoliated sheets together with the formulation of functional inks and the current development of printing/coating processes of interest for the realization of 2D-crystal-based devices.
Gesehen am 14.05.2020